2017
DOI: 10.1038/nature24677
|View full text |Cite
|
Sign up to set email alerts
|

Orbital misalignment of the Neptune-mass exoplanet GJ 436b with the spin of its cool star

Abstract: The angle between the spin of a star and the orbital planes of its planets traces the history of the planetary system. Exoplanets orbiting close to cool stars are expected to be on circular, aligned orbits because of strong tidal interactions with the stellar convective envelope. Spin-orbit alignment can be measured when the planet transits its star, but such ground-based spectroscopic measurements are challenging for cool, slowly rotating stars. Here we report the three-dimensional characterization of the tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
177
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(191 citation statements)
references
References 33 publications
14
177
0
Order By: Relevance
“…Alternatively, a distant companion can excite the eccentricity, and as the Neptune-size planet migrates closer to the star, it would evaporate increasingly and erode into a smaller planet before it can fully circularize, thus explaining why no Neptune-mass planets are found on circular orbits close to their star. This combination of high-eccentricity migration and evaporation as the origin of eccentric warm Neptunes was proposed by Bourrier et al (2018a), based on the study of GJ 436b, and is now gaining interest to explain the structure of the "Neptune desert" (e.g., Owen & Lai 2018). In this scenario, the warm Neptunes on eccentric orbits are either still undergoing their migration and will erode as they enter the desert or they have already reached a stable orbit far enough from the star to be safe from evaporation.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Alternatively, a distant companion can excite the eccentricity, and as the Neptune-size planet migrates closer to the star, it would evaporate increasingly and erode into a smaller planet before it can fully circularize, thus explaining why no Neptune-mass planets are found on circular orbits close to their star. This combination of high-eccentricity migration and evaporation as the origin of eccentric warm Neptunes was proposed by Bourrier et al (2018a), based on the study of GJ 436b, and is now gaining interest to explain the structure of the "Neptune desert" (e.g., Owen & Lai 2018). In this scenario, the warm Neptunes on eccentric orbits are either still undergoing their migration and will erode as they enter the desert or they have already reached a stable orbit far enough from the star to be safe from evaporation.…”
Section: Discussionmentioning
confidence: 79%
“…Spectacular evaporation has been observed for the warm Neptunes GJ 436 b (Bourrier et al 2018a) and GJ 3470 b (Bourrier et al 2018b). This class of planets is expected to be particularly sensitive to atmospheric escape (Owen & Wu 2017).…”
Section: Discussionmentioning
confidence: 97%
“…This contrasts with the planet GJ 436b, whose exosphere is shaped by the combination of radiative braking and charge-exchange with the low-velocity (∼55 km s −1 ) wind of its host star (Bourrier et al 2016). Since GJ 3470 is an earlier-type, younger M dwarf than GJ 436 (which has an age greater than 4 Gyr, Bourrier et al 2018, Veyette & Muirhead 2018, its stellar wind might be faster than the observable range of the stellar Lyman-α line (∼200 km/s), which would explain why stellar wind protons neutralized by charge-exchange with the exosphere absorb too far in the wing to be detectable. Nonetheless the wind from GJ 3470 could still have an influence on the upper atmosphere of its planet, for example via the formation of a mixing layer (see Sect 6.3.1).…”
Section: Influence Of Radiation Pressure and Stellar Windmentioning
confidence: 99%
“…Assuming a Q p = 10 6 , GJ 436 b would have initially orbited with an eccentricity around ∼0.8 at a distance of ∼0.05 AU. However, this scenario does not explain the high obliquity of the current orbit reported by Bourrier et al (2018).…”
Section: Gj 436mentioning
confidence: 76%
“…The old age of GJ 436 is surprising considering that it hosts a short-period planet in an eccentric orbit (e = 0.152±0.009, Trifonov et al 2018). Bourrier et al (2018) recently reported that the orbit of GJ 436 b is not only eccentric, but also nearly perpendicular with the spin axis of the star.…”
Section: Gj 436mentioning
confidence: 99%